Mg-Fe-RICH AMPHIBOLES ASSOCIATED TO PYROCLASTICS FROM SANTORINI ISLAND, SOUTH AEGEAN SEA VOLCANIC ARC, GREECE - Kitsopoulos, K. (Bulletin of the Geological Society of Greece, 2007)
Amphibole bearing volcanic products in Santorini are restricted to the early volcanic activity expressed in the Akrotiri peninsula. This fact distinguishes these early products from the rest of the volcanic rocks of Santorini. The Fe-Mg-rich mineral phases, associated to the Akrotiri silicic pyroclastics which were analysed can be classified as Mg-Fe rich type of amphibole. This type of amphibole has not been reported before in volcanic rocL· from the South Aegean Volcanic Arcr. The presence of such a high Fe-Mg mineral phase in silicic pyroclastics in Santorini is constant with the involvement of primitive, mantle derived, mafic magmas, with some considerable water content, and which have been differentiated, before they are mixed with more silicic magmas at a shallower crustal level.